Impact of examined lymph node counts on survival of patients with stage IA non-small cell lung cancer undergoing sublobar resection - Liu, Yang; Shen, Jianfei; Liu, Liping; Shan, Lanlan; He, Jiaxi; He, Qihua; Jiang, Long; Guo, Minzhang; Chen, Xuewei; Pan, Hui; Peng, Guilin; Shi, Honghui; et al. (Journal of Thoracic Disease, 2018)
Background: The correlation between the number of examined lymph nodes (ELNs) and lung cancer-specific survival (LCSS) of stage IA non-small cell lung cancer (NSCLC) patients, who underwent sublobar resection in which lymph node (LN) sampling was relatively restricted as compared with standard lobectomy remains unclear. Methods: Patients from the Surveillance, Epidemiology, and End Results database with stage IA NSCLC who underwent sublobar resection were categorized based on ELN count (1–6 vs. ≥7; the cut point 7 was identified by Cox model). Results: Collectively, 3,219 patients with a median follow-up time of 37 months were included in this study (G1: 1–6 ELN, n=2,410; G2: ≥7 ELN, n=809). The 5-year LCSS rate of the G1 and G2 cohorts were 75% and 83%, respectively. Cox analysis suggested that the LCSS of G1 cohort patients was lower as compared with the G2 cohort [hazard ratio (HR) =1.530; 95% confidence interval (CI): 1.240–1.988, P